2017
DOI: 10.1002/stem.2755
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Approach to Single Cell RNA-Sequence Analysis Facilitates In Silico Gene Reporting of Human Pluripotent Stem Cell-Derived Retinal Cell Types

Abstract: Cell type-specific investigations commonly use gene reporters or single-cell analytical techniques. However, reporter line development is arduous and generally limited to a single gene of interest, while single-cell RNA (scRNA)-sequencing (seq) frequently yields equivocal results that preclude definitive cell identification. To examine gene expression profiles of multiple retinal cell types derived from human pluripotent stem cells (hPSCs), we performed scRNA-seq on optic vesicle (OV)-like structures cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(102 citation statements)
references
References 30 publications
3
97
2
Order By: Relevance
“…Our results suggest differential expression patterns among the seven markers. All seven rod markers are highly abundant, consistent with previous scRNA-seq studies of mouse and human retina (Macosko et al, 2015;Phillips et al, 2018). The seven markers showed differential expression patterns in the six identified rod photoreceptor clusters.…”
Section: Profiling Healthy and Degenerating Human Rod Photoreceptor Ssupporting
confidence: 87%
See 1 more Smart Citation
“…Our results suggest differential expression patterns among the seven markers. All seven rod markers are highly abundant, consistent with previous scRNA-seq studies of mouse and human retina (Macosko et al, 2015;Phillips et al, 2018). The seven markers showed differential expression patterns in the six identified rod photoreceptor clusters.…”
Section: Profiling Healthy and Degenerating Human Rod Photoreceptor Ssupporting
confidence: 87%
“…Correlation matrix to benchmark hiPSC‐derived cone photoreceptors (week 15 and week 20; Welby et al , ), fetal cone photoreceptors (Welby et al , ), adult retina (Phillips et al , ), and the human Müller glia cell line MIO‐M1 against all retinal cell types identified in this human neural retina atlas.…”
Section: Resultsmentioning
confidence: 99%
“…Our results suggest differential expression patterns among the 7 markers. All 7 rod markers are highly abundant, consistent with previous scRNA-seq studies of mouse and human retina (Phillips et al, 2018;Macosko et al, 2015). The 7 markers showed differential expression patterns in the 6 identified rod photoreceptor clusters.…”
Section: Profiling Healthy and Degenerating Human Rod Photoreceptor Ssupporting
confidence: 81%
“…To demonstrate the use of our dataset as a benchmarking reference, we compared the scRNA-seq profiles of distinct cell types generated using alternative methods, including fetal human cone photoreceptors, human induced pluripotent stem cell derived-cone photoreceptors (hiPSC-cone; (Welby et al, 2017), and a sample of adult human retina with 139 cells (Phillips et al, 2018). Correlation analysis demonstrated that the adult human retina sample showed highest similarity to rod photoreceptor (0.63, Supplementary figure 10), which is expected as rod photoreceptors represent the majority of the cells in the retina.…”
Section: Using the Human Neural Retina Transcriptome Atlas For Benchmmentioning
confidence: 99%
See 1 more Smart Citation